PENGARUH INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM DI ANJUNGAN CEMPAE - RYAN, RYAN HIDAYAT (IAIN Parepare, 2024)
ABSTRACT This research aims to determine the influence of financial inclusion and financial literacy on the performance of SME. This research uses the July 2019 Quantitative Associative research type. The data collection method was carried out by distributing questionnaires to 102 respondents, namely SME entrepreneurs in Anjuangan Cempae Parepare city.